Rekontruksi Kurikulum Pondok Pesantren di Era Globalisasi - Ali Mu'tafi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: For pesantren as a system of education has many problems in facing globalization, many efforts should be done. Among many, curriculum of pesantren becomes the most important aspects to be reconstructed within global perspective since curriculum as one of the most fundamental rute in handling the process of education. Therefore, this paper actually tries to elaboraate the problem of pesantren curriculum in facing globalization and then tries to promote alternative model of curriculum construction. Using sosio-historical perspective, the alternative mcdel oi curriculum reconstruction is done by integrating between both traditional and modern system of education. Keywords: Pesantren, curriculum, tradisional, globalisasi, and reconstruction.